Large, but Dispersal‐Limited Populations of the Marsh Fritillary Euphydryas aurinia Persist on Abandoned Military Training Areas Three Decades After the End of the Cold War - Cindy Schröer; David Singer; Johannes Kamp (Ecology and Evolution)
ABSTRACT Military training areas can host important biodiversity, due to the preservation of diverse, nutrient‐poor historical cultural landscapes and an insect‐friendly disturbance regime. In Europe, many training areas were abandoned after the end of the cold war in 1991 and the withdrawal of the Allied and Soviet forces. Many of these are now protected areas, and current management strategies vary from rewilding to active habitat management such as grazing or mowing. In a capture–release–recapture approach, marking 2418 individuals, we assessed the population size and movement patterns of the dry ecotype of the Marsh Fritillary Euphydryas aurinia Rottemburg 1775 on three former military training areas in Germany that varied in size and management (natural succession, mowing, and sheep‐/goat grazing). Euphydryas aurinia is a rare and declining butterfly species listed in Annex II of the European Union Habitats Directive. Jolly–Seber models revealed a large population of ca. 19,000 individuals on the largest study site and a smaller population at a second site, whereas recapture rates were too low to predict the population size reliably at a third site. Population densities were 190–194 butterflies ha−1 at the unmanaged, large site and 56–71 butterflies ha−1 at a smaller site grazed with sheep. Thirty‐nine percent of the recapture events occurred within the same 1‐ha‐study plot. The average minimum flight distance between the study plots was 313 m for males and 328 m for females. The maximum lifetime flight distance was 1237 m within 3 days. No dispersal was detected between study sites. Thirty years after cessation of the military use, the large former training site still held what likely is one of the largest populations of the species dry ecotype in Central Europe, including in areas where management ceased already in 1991. This suggests remarkable persistence of the species in areas without regular management, contrary to current opinion. However, regular flight distances seem not to be sufficient to connect the isolated habitat patches. It remains unknown how long the large population at the abandoned military area will persist without active habitat management. Careful, but active habitat management and restoration of habitat connectivity should thus be considered.